Analisis Strategi Penanganan Risiko (Mitigasi, Transfer,Hindari) - Gloria Sthefany; Grace Putri Johana Rajagukguk (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
This study aims to analyze risk treatment strategies, including risk mitigation, risk transfer, and risk avoidance, as essential components of organizational risk management. The research employs a literature review method by examining various relevant scientific sources related to the concepts and implementation of risk treatment strategies. The findings indicate that risk mitigation is carried out through efforts to reduce the likelihood of risk occurrence and its potential impact. Risk transfer is implemented by shifting part of the potential losses to other parties, such as insurance companies or business partners. Meanwhile, risk avoidance is undertaken by refraining from engaging in activities that involve a high level of risk. The integrated application of these three strategies can assist organizations in maintaining operational stability, protecting assets, enhancing decision-making effectiveness, and supporting long-term business sustainability.